2019
DOI: 10.1002/ajp.23022
|View full text |Cite
|
Sign up to set email alerts
|

Maternal influence on the development of nut‐cracking skills in the chimpanzees of the Taï forest, Côte d'Ivoire (Pan troglodytes verus)

Abstract: Chimpanzees' (Pan troglodytes) nut-cracking behavior represents one of the most complex forms of tool-use known among nonhuman animals. Given the close phylogenetic relationship between these apes and humans, investigating how such complex behavior develops in immatures can reveal the evolutionary roots of the cognitive processes that enabled the evolution of outstanding technological skills in our lineage. In this study, we investigated whether maternal behavior directly enhanced nut-cracking skills in immatu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
47
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(49 citation statements)
references
References 60 publications
1
47
0
1
Order By: Relevance
“…nut-cracking performance (14). In the Goualougo Triangle, Republic of Congo, transfers of termite-fishing probes from skilled to less-competent conspecifics satisfy functional criteria for teaching (17): transfers occur in the presence of a learner; they impose a cost on tool donors, in the form of reduced tool use and feeding; and they provide a benefit to tool recipients, who show increased tool use and feeding after receiving a tool.…”
Section: Significancementioning
confidence: 99%
See 2 more Smart Citations
“…nut-cracking performance (14). In the Goualougo Triangle, Republic of Congo, transfers of termite-fishing probes from skilled to less-competent conspecifics satisfy functional criteria for teaching (17): transfers occur in the presence of a learner; they impose a cost on tool donors, in the form of reduced tool use and feeding; and they provide a benefit to tool recipients, who show increased tool use and feeding after receiving a tool.…”
Section: Significancementioning
confidence: 99%
“…In an experiment with human children, success at solving tasks of increasing difficulty varied with the number of prosocial acts received, suggesting that prosocial helping could facilitate social transmission of complex tasks (2). Chimpanzees have been observed transferring tools in numerous contexts in the wild (11,15,14,18,(29)(30)(31). However, no standardized comparisons have been conducted to evaluate whether and how this form of scaffolding varies between populations and across tasks of differing complexity.…”
Section: Significancementioning
confidence: 99%
See 1 more Smart Citation
“…However, our study also consisted of various social learning test conditions-including one that demonstrated the necessary action patterns for nut-cracking to the chimpanzees. This condition allowed for the possibility of action copying being a requirement of the behaviour, as has recently been claimed (Estienne et al, 2019). Even so, nut-cracking was not acquired by the subjects.…”
Section: Discussionmentioning
confidence: 86%
“…Indeed, recent research in wild chimpanzees shows an exponential increase in nut-cracking between 5 and 6 years of age, though the first signs were observed in 3-4-year-old individuals (Estienne et al, 2019) in line with the concept of maturation (Corp & Byrne, 2002). This finding suggests a certain level of developmental prowess required to express nut-cracking, perhaps somewhere between maturation effects of the body and the brain.…”
Section: Sensitive Learning Periodmentioning
confidence: 82%